Transition economies and foreign trade - Winiecki, Jan. (London ; New York : Routledge, 2002)
By taking the distortions of the Communist era into consideration, the book explains the phenomenon of the decline in output and trade, as well as explaining the dual commodity nature of exports in the early transition phase.
Includes bibliographical references and index.
oif 18/09/15
Loan
Keywords: Exports -- Europe, Eastern; Exports -- Europe, Central; International trade; Europe, Eastern -- Commerce; Europe, Central -- Commerce; Europe, Eastern -- Economic conditions -- 1989-; Europe, Central -- Economic conditions -- 20th century